2011
DOI: 10.1128/jcm.01230-11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genomic Sequence Variability on Quantitative PCR Assays for Diagnosis of Polyomavirus BK Infection

Abstract: Knowledge of polyomavirus BK (BKV) genomic diversity has greatly expanded. The implications of BKV DNA sequence variation for the performance of molecular diagnostic assays is not well studied. We analyzed 184 publically available VP-1 sequences encompassing the BKV genomic region targeted by an in-house quantitative hydrolysis probe-based PCR assay. A perfect match with the PCR primers and probe was seen in 81 sequences. One Dun and 13 variant prototype oligonucleotides were synthesized as artificial targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 16 publications
2
38
0
1
Order By: Relevance
“…Our findings raise the interesting question of whether different BKV genotypes or subgenotypes exhibit altered tissue tropism or different levels of virulence in vivo. Although previous studies have surveyed BKV genotypes found in nephropathic lesions (15,16,(37)(38)(39), these studies have relied on BKV-I-biased PCR primers that underestimate the abundance of BKV genotypes II, III, and IV (40). The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings raise the interesting question of whether different BKV genotypes or subgenotypes exhibit altered tissue tropism or different levels of virulence in vivo. Although previous studies have surveyed BKV genotypes found in nephropathic lesions (15,16,(37)(38)(39), these studies have relied on BKV-I-biased PCR primers that underestimate the abundance of BKV genotypes II, III, and IV (40). The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…We mostly evaluated patients with genotypes Ib1, Ib2, and IV, the most prevalent genotypes in our center and in Europe. It has been demonstrated clearly that some BKV quantification assays present decreased sensitivity for detection of less common subtypes of BKV, including genotypes II and Ic (12,13). It may therefore be useful to conduct further investigations with these rarer genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Most in-house quantitative PCR tests for BKV developed several years ago used the Dunlop strain (genotype I) as a reference sequence for the selection of primers and probes (13). Real-time PCR determination of VL is based on the primer amplification efficiency, the efficiency of hybridization of the primers and probes for the enzymatic cleavage, and finally the amplification efficiency relative to the target in the reference material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations